Game based learning in a psychology classroom - Sidra Naim; Norizan Abdul Razak (Penerbit Universiti Kebangsaan Malaysia, 2023)
Game based learning is gaining acceptance in the classroom as it is a platform for students’ engagement and immediate feedback which are very valuable. However, as creating such game platforms is very time- intensive, requires experience, as well as a big budget, the use of gamification within a higher institution tends to be minimal. This study looks at a gamification platform that requires minimal instructor investment, and limited instructor or students training, a quiz can be generated and played within minutes. This paper focused on the classroom dynamics, the students’ engagement, the students’ motivation and the features that affect learning in terms of using the gamification platform. This qualitative paper will present the findings of students engaging in active learning using gamification in Psychology of Thinking class as well as the observations of the educator throughout the sessions. This paper’s findings are useful to add to literature on the usage of gamification in a psychology classroom.